The Belarusian language as an integral part of history and modernity of the Belarusian State University - Pryhodzich, Mikalai R. (Journal of the Belarusian State University. Philology, 2021)
The article examines the history of formation of the Belarusian language and Belarusian linguistics at the Belarusian State University during 1921–2021; examines the achievements of university linguists in various areas of the theory and practice of teaching linguistics courses, preparing monographic and practice-oriented textbooks and teaching aids, focuses on the work of foreign Belarusianists, participation of Belarusian State University scientists in international projects, including work of international congresses of Slavists. The article analyses the results of fruitful cooperation between teachers of the department of Belarusian linguistics and scientists of the Jakub Kolas Institute of Linguistics of the National Academy of Sciences of Belarus, joint scientific conferences and readings, preparation of dictionaries, collective monographs and manuals on various academic disciplines. The role of university linguists and the staff of the academic institute in the study of the history of formation of Belarusian linguistics as a scientific direction, training of highly qualified personnel, development of normative documents in the field of the functioning of the modern Belarusian literary language is evaluated. The article considers the prospects of studying the issues of further development of the Belarusian language both at Belarusian State University and in the Republic of Belarus, in the near and far abroad.